Creating Future Leaders Program 2.0 - Anita, Abdul Rani (2019)
Pekan, 30th March 2019 - The Soft Skills Department had never given up in developing students’ soft skills. This time around, the department’s program was to help students to change change their attitudes to succeed in academic and as well as pious Muslims. Creating Future Leaders Workshop 2.0 had been held in Kem Azam Training Center on 30, 31 March 2019 with the attendance of 17 students from different faculties.